Arm-Hand Boost Therapy During Inpatient Stroke Rehabilitation: A Pilot Randomized Controlled Trial - Meyer, Sarah; Verheyden, Geert; Kempeneers, Kristof; Michielsen, Marc (Frontiers in Neurology, 2021)
Objective: It was the aim to assess feasibility, safety and potential efficacy of a new intensive, focused arm-hand BOOST program and to investigate whether there is a difference between early versus late delivery of the program in the sub-acute phase post stroke. Methods: In this pilot RCT, patients with stroke were randomized to the immediate group (IG): 4 weeks (4w) BOOST +4w CONTROL or the delayed group (DG): 4w CONTROL +4w BOOST, on top of their usual inpatient care program. The focused arm-hand BOOST program (1 hour/day, 5x/week, 4 weeks) consisted of group exercises with focus on scapula-setting, core-stability, manipulation and complex ADL tasks. Additionally, one hour per week the Armeo®Power (Hocoma AG, Switzerland) was used. The CONTROL intervention comprised a dose-matched program (24 one-hour sessions in 4w) of lower limb strengthening exercises and general reconditioning. At baseline, after 4 and 8 weeks of training, the Fugl-Meyer assessment upper extremity (FMA-UE), action research arm test (ARAT) and stroke upper limb capacity scale (SULCS) were administered. Results: Eighteen participants (IG: n=10, DG: n=8) were included, with a median (IQR) time post stroke of 8.6 weeks (5-12). No adverse events were experienced. After 4 weeks of training, significant between-group differences were found for FMA-UE (p=0.003) and SULCS (p=0.033) and a trend for ARAT (p=0.075) with median (IQR) change scores for the IG of 9 (7-16), 2 (1-3) and 12.5 (1-18) respectively, and for the DG of 0.5 (-3-3), 1 (0-1) and 1.5 (-1-9), respectively. In the IG, 80% of patients improved beyond the minimal clinical important difference of FMA-UE after 4 weeks, compared to none of the DG patients. Between 4 and 8 weeks of training, patients in the DG tend to show larger improvements when compared to the IG, however, between-group comparisons did not reach significance. Conclusions: Results of this pilot RCT showed that an intensive, specific arm-hand BOOST program, on top of usual care, is feasible and safe in the sub-acute phase post stroke and suggests positive, clinical meaningful effects on upper limb function, especially when delivered in the early sub-acute phase post stroke. Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT0458417